Towards the integration of process and quality control using multi-agent technology - Castellini, Paolo (2012)
The paper introduces a vision on the design of distributed manufacturing control systems using the multi-agent principles to enhance the integration of the production and quality control processes. It is highlighted how agent technology may enforce interaction of manufacturing execution system and distributed control system, enhancing the exploitation of the available information at the quality control and process control levels. A specific focus is made on a suitable engineering methodology for the design and realization of such concept. Innovation is also presented at the level of adaptive process control and self-optimizing quality control, with examples related to a home appliance production line.